Striking a Balance: Navigating Economic Growth and Sustainability in Indonesia’s Palm Oil Sector - Jo Anastasya, Imelda; Angelica, Tiffany (Law Review, 2024)
Indonesia’s palm oil plantations have an irreplaceable role in Indonesia’s economy, contributing to job creation, rural poverty reduction, export revenue, and gross domestic product. Although such exploitation of its natural resources is within Indonesia’s permanent sovereignty, developed countries have expressed environmental concerns over Indonesia’s surge in palm oil expansion, which has brought about deforestation, biodiversity loss, and greenhouse gas emissions. This research will analyze whether Indonesia can navigate economic growth and sustainability in its palm oil sector, amidst such conflicting interests. Utilizing a normative legal research methodology with a statute approach, relevant laws, regulations, and practices will be used to identify whether Indonesia can achieve a sustainable palm oil industry that aligns with national development goals while also adhering to global environmental standards, ensuring both economic growth and sustainability.